Joao Antonio: a tie-down of the decolonial voice - Silva, Claudia Maria Cantarella [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2024)
In 1960, Jo & atilde;o Ant & ocirc;nio wrote that, for him, in snooker, the tie-down is an experienced partner, because he knows how to keep himself to himself. The objective of this article is, therefore, to discuss how the poetic and, at the same time, tie-down gaze of the journalist and writer Jo & atilde;o Ant & ocirc;nio skillfully penetrates the marginal veins to portray to the reader the coloniality rooted in the lives of those who inhabit the outskirts in the author's writing. Snooker players, street kids, car park attendants, among other marginalized take over the speech in the stories, parade their own language and lead us, not only to reality in reverse, but also to the poetics of the writer's unique way of telling. We believe that the voice emanating from the subaltern characters represents the decolonial thought, in the broadest sense, by translating to literature the resistance of those who adapt to the adversities of a social system that debases them and leads them to the need to establish collusions in order to survive. To this end, we selected the writer's short stories Menin & atilde;o do Caixote, from his debut book Malagueta, Perus e Bacana & ccedil;o (1963) and Guardador (1992), from the homonymous work. Regarding the concepts of Coloniality / Decoloniality, we will use the studies of Anibal Quijano, Nelson Maldonado-Torres, Walter Mignolo and Luciana Ballestrin.
Keywords: Joao Antonio; Coloniality; Decolonial voice; Marginal life